Perbuatan Melawan Hukum Atas Lelang Jaminan Hak Tanggungan (Studi Kasus Putusan Mahkamah Agung Nomor 2715 K/PDT/2018) - Mangisara Darmawan Siagian (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractMortgage rights to land along with objects related to land, are guarantee rights which are imposed on land rights as mentioned in Law Number 5 of 1960 concerning Basic Regulations on Agrarian Matters, whether or not following other objects constitute one unit with the land, to pay off certain debts, which gives certain creditors priority over other creditors.The problems in this study are: the terms of an auction that can meet the onrechtmatige daad, the auction that violates the provisions of the law, legal considerations by the judge in the execution auction in the decision of the Supreme Court Number 2715 K / PDT / 2018.This research is descriptive with a normative juridical approach.